Ergonomic solutions for the process industries - Attwood, Dennis A. (Gulf Professional Pub., 2004)
Work-related injuries, such as back injuries and carpal tunnel syndrome, are the most prevalent, most EXPENSIVE, and most preventable workplace injuries, accounting for more than 647,000 lost days of work annually (according to OSHA estimates). Such injuries, and many others, can be prevented in your facility by establishing an ergonomic design. This book shows you how to apply simple Ergonomic tools and procedures in your plant. Challenging worldwide regulations are forcing some companies to spend thousands of dollars per affected employee in order to comply. This book shows you how to comply with these regulations at a fraction of the cost, in the most timely, efficient method possible. *Learn how to use the Human Factors/Ergonomics tools in process industries *Identify and prioritize Ergonomic issues, develop interventions, and measure their effects *Apply Ergonomics to the design of new facilities.